Mapping of geochemical contamination in Urban areas of Lithuania - Gregorauskienė, Virgilija (Journal of Environmental Engineering and Landscape Management, 2006)
In Lithuania geochemical mapping of urban areas was started in Vilnius city in 1985. Topsoil, stream sediments, snow cover, manufactory dust and other sampling media are used in ecogeochemical investigations. The aim of investigations is to detect sources of pollution, its geochemical properties and spread of its contamination. Furthermore, a sanitary assessment of urban soil is carried out on the basis of available geochemical data and the soil quality standard of Lithuania HN 60:2004. The soil contamination with heavy metals is estimated according to the highest allowable concentrations (HAC) and the total contamination index Zd which is related to the criteria of human health. At present the geochemical data on soil contamination in the areas of Vilnius, Panevëžys, Mažeikiai, Šiauliai, Alytus, Biržai, Pasvalys, Rokiškis, Kupiškis and other towns are in store of the geochemists of Geological Survey of Lithuania and Institute of Geology and Geography. The soil geochemical background values obtained by geochemical mapping of natural areas are always used for assessment of contaminated urban areas. Part of geochemical background and contamination data is published in Geochemical Atlas of Lithuania. Some geochemical data and soil contamination maps are in use of town municipalities on order and funds of which the geochemical investigations of urban areas were performed. However, geochemical investigations lag behind the planning, development and reclamation projects of urban areas, thus, new dwelling houses are often built on hazardous contaminated sites that may make a threat against human health. Article in Lithuanian. Geocheminės taršos Lietuvos miestuose kartografavimas Santrauka. Ekologinis geocheminis miesto teritorijų kartografavimas prasidėjo 1985 m. Vilniuje. Šių geocheminių tyrimų tikslas – nustatyti taršos šaltinius, pobūdį ir sklaidą. Tiriamas viršutinis dirvožemio sluoksnis, vandens telkinių dugno nuosėdos, sniego danga, įmonių dulkės ir kitos terpės. Miesto grunto tarša įvertinama lyginant nustatytuosius cheminių elementų kiekius su didžiausiomis leistinosiomis koncentracijomis DLK, pateiktomis Lietuvos higienos normoje HN 60:2004, arba pagal skaičiuojamą suminį užterštumo rodiklį Zd , kuris labai susijęs su gyventojų sveikatingumo parametrais. Vilniaus, Panevėžio, Mažeikių, Šiaulių, Alytaus, Biržų, Pasvalio, Rokiškio, Kupiškio ir kitų miestų dirvožemio taršos duomenys yra saugomi Lietuvos geologijos tarnybos bei Geologijos ir geografijos instituto duomenų bazėse. Nustatant taršos lygį naudojami dirvožemio foniniai duomenys, gaunami kartografuojant gamtines teritorijas. Apibendrintieji dirvožemio cheminės sudėties duomenys šalies mastu publikuoti Lietuvos geocheminiame atlase, o kai kuriais duomenimis naudojasi tik miestų savivaldybės, kurių užsakymu buvo atlikti atitinkami tyrimai. Deja, geocheminiai dirvožemio tyrimų duomenys dar nėra pakankamai efektyviai naudojami rengiant regionų ir miestų plėtros planus, todėl naujos statybos gyvenamieji namai dažnai iškyla pavojingai užterštose vietovėse, nepalankiai veikiančiose žmogaus sveikatą. Reikšminiai žodžiai: geochemija, miesto dirvožemiai, užterštumas, sunkieji metalai, suminis užterštumo rodiklis Zd . First Published Online: 14 Oct 2010